Assessing Economic Carrying Capacity through Financial Feasibility Analysis for Sustainable Seaweed and Pearl Oyster Mariculture in the Dampier Strait Conservation Area - Ichsan Suryo Wibowo; Ali Mashar; Niken Tunjung Murti Pratiwi; Fery Kurniawan; Al Izzha Kusumaningtyas; Istna Nabila Zulfa; Masruhin Masruhin (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2026)
A financial feasibility analysis in mariculture activities is necessary to ensure the business can provide economic benefits and operate sustainably. The Dampier Strait Conservation Area has the potential to develop seaweed and pearl oyster cultivation businesses. However, as a conservation area, its utilization must consider environmental carrying capacity. This study aims to assess the financial feasibility of seaweed and pearl oyster cultivation in the Dampier Strait Conservation Area as a basis for optimal, environmentally friendly business planning that provides economic benefits for the local community. Financial feasibility is measured using a cost-benefit analysis method. The first step is to determine the efficiency of component use and cost structure in the aquaculture business planning scheme. The results of the cost and benefit calculations are used to determine the capacity for developing the aquaculture business, which includes an assessment of several aspects of future investment. Based on the results of the cost-benefit analysis, the marine aquaculture business for both commodities is feasible for development, having met business feasibility requirements based on the comparison of cost and benefit values, the percentage of profit, the rate of return on assets, the difference and comparison between expenses and revenues, and the payback period. All stages of the analysis have been able to produce comprehensive results to achieve optimal and sustainable utilization of the area through the development of mariculture activities. This has taken into account the continuity between environmental potential and human demands for utilizing ecosystem services in an integrated manner.